Relational goods, monitoring and non-pecuniary compensations in the nonprofit sector: the case of the Italian social services - Michele Mosca; Marco Musella; Francesco Pastore (Institute for the Study of Labor (IZA), 2006)
This paper investigates the nonprofit wage gap suggesting a theoretical framework where, like in Akerlof (1984), effort correlates not only with wages, but also with non-monetary compensations. These take the form of relational goods and services by-produced in the delivery of particular services. By paying higher non-pecuniary compensations, the nonprofit sector attracts intrinsically similarly skilled, but more motivated workers, able to provide in fact a higher level of effort than their counterparts in the forprofit sector. On an empirical ground, the paper provides a number of econometric tests that confirm the main predictions of the model in Italy's case. It adds to the available empirical literature by introducing in the analysis direct measures of non-pecuniary compensations and job satisfaction.
Keywords: I00; J31; L31; L84; 330; relational goods; job satisfaction; wage determination; non-profit organisations; efficiency wages